International Standards for the Safety of Persons Assisting in Criminal Justice - Ignatenko, Evgeniy A.; Lyakhova, Anzhelika I.; Lukyanchikova, Elena F.; Savelieva, Irina V.; Starodubova, Galina V. (Cuestiones Políticas, 2020)
The objective of the research was to analyze some international standards for the safety of people who attend criminal justice from different approaches and perspectives of analysis. Based on a meaningful analysis of the provisions of international and regional regulatory legal acts, the document presents approaches to the formation of standards to ensure the safety of persons who contribute to criminal justice. Methodologically, the work applied the provisions of dialectics, general, special and particular scientific methods. In the course of the study, scientific-historical, formal-legal, formal-logical, systemic and comparative methods were also used. It is concluded that the system of security measures for people who cooperate with criminal justice has significant differences in the different national criminal justice systems, which complicates international relations and cooperation in this area and does not allow the international community to advise effectively and comprehensively, while continuously generating challenges and threats.